Urban design in underground public spaces: lessons from Moscow Metro. Issue 4 (4th July 2022) - Lee, Jae Min
ABSTRACT: This paper examines the history and social life of the underground public spaces in three Moscow Metro stations just north of Red Square and the Kremlin: Okhotny Ryad, Tverskaya, and Ploshchad Revolyutsii stations. Moscow's subway originated from two motivations: to improve the public transit system and to revitalize Moscow's centre instead of moving out to the suburbs for growth. To achieve these goals, subway architects and planners devised beautiful and people-friendly subway stations that cannot be observed in other Western cities. The resulting spaces successfully accommodated a high level of social activities in the central halls of the platforms as well as on escalators. Several urban design principles, including "soft edge" and "triangulation props", can be observed regardless of the designers' original intent. Moscow's subway stations are case studies worth exploring before architects and planners design their underground systems.